Fish Assemblage and Impact of Oscillation Between Drowning and Drought on Fish Size-Spectrum in the Al-Chibyaish Marsh, Southern Iraq - Abdullah, Abdul Hussein Jaafer (Iraqi Journal of Science, 2019)
The present study was implemented in the period from January to December 2017, to assess the assemblage of fish, with the effects of some environmental factors and knowledge the impacts of annual periodic fluctuations between drowning and drought on the abundance and size-spectrum on the fish community in Al-Cibyaish marsh. Water temperature ranged between 13 ͦ C in January to 35 ͦ C in July, salinity from 2.90 PSU (Practical salinity unite) in February to 4.14 PSU in August. Hydrogen ion ranged between 7.60 in July to 8.30 in February. The present study appears contribution of environmental variables in the distribution, widespread and occurrence of fish assemblage in the Al-Chibyaish marsh. A total of 3294 specimens were collected represented 15 fish species affiliated to 15 genera, six families and five orders. Three fish species in present area were formed 72.38% of the total number of species in the marsh. Planiliza abu was the most abundant species formed 35.43%, Alburnus mossulensis, 19.22% and Oreochromis aureus, 17.73%. The ecological indices were within the range of previous studies and described as poor for diversity index ranged between1.38 in June to 1.96 in November. Richness index fluctuated from 0.96 in May and July to 1.96 in April and can express as half integrated. The evenness index values ranged from 0.68 in September to 0.85 in November and December indicate to semi-balanced or slightly balanced. Fish size revealed dominance of the small size due to high mortality in the dry season. The present study affirms prevalence and dominates of historical small native species P. abu and some of the small invasive species, which possess various functional characteristics, enable it to inhabit the marsh.